An Anishinaabe Tradition: Anishinaabe Constitutions in Ontario - Derynck, Leaelle N. (Scholarship@Western, 2020)
Constitutionalism is an Anishinaabe legal tradition. This thesis explores modern Anishinaabe constitutions in Ontario, as they connect to traditional constitutionalism while meeting the unique governing needs of contemporary Anishinaabe First Nations communities. I address the scholarly and legal context in which these constitutional documents have been produced and shed an empirical light on these understudied legal instruments. Two questions shape this thesis: 1) what are the defining characteristics of Anishinaabe constitutions in Ontario; and, 2) what is their function within Anishinaabe communities? To answer these questions, I review both ratified and draft Anishinaabe constitutional documents of member communities of the Anishinabek Nation according to three elements of constitutional development: culture, power, and justice. I find that these constitutions, though comparable to Western constitutions, are distinctly Anishinaabe legal instruments that respond to the settler-colonial state while prioritizing the restoration of Anishinaabe law-making powers and jurisdiction. Modern, positivist Anishinaabe constitutions in Ontario seek to nourish Anishinaabe ways of living as they look toward the past, present, and future needs of the communities that produce them. I conclude that, whatever the state of current scholarly discussions on the theoretical compatibility of Indigenous law with state law, these constitutions exist as a form of practical self-empowerment.